(untitled) (Third Sector Social Economic Review, 2020)
The aim of this study is to determine the relationship between the charismatic leadership characteristics of SME employees and managers and social capital. Survey model, one of the quantitative research models, was used in the research. The universe of the research consists of the employees in Small and Medium-sized Enterprises working in the Marmara Region. The sample group of the research consists of employees in Small and Medium-sized Enterprises in Istanbul. Charismatic Leadership and Social Capital scales were used as data collection tools in the research. Descriptive statistical analysis, t-test and ANOVA test were used to analyze the data of the study. It is seen that there is no significant relationship between the gender and professional seniority of SME employees and the dimensions in Charismatic Leadership and Social Capital Scale. SME employees state that the more they value themselves and the sensitivity of other members in the business, the more the communication level between managers and employees improves. SME employees express that managers who are visionary, sensitive to the environment, exhibit extraordinary behaviors, take personal risks, are sensitive to member needs, and who do not maintain the status quo make their employees more adapt to social norms and increase their sense of communication and trust.